Intipan siber: Jenayah baru dalam masyarakat kontemporari - Asiah, Bidin; Shariffah Nuridah Aishah, Syed Nong Mohamad; Akmal, Mohamad (2015)
Innovation and technological advancement nowadays had produced several web-based products. These include social networking sites (SNS) which are dominating Internet usage among consumers. Although the site is able to connect friendship without limits and become a very effective means of communication in cyberspace, the negative impact should not be under-estimated. This article concludes that the use of social networking sites gives the risk of the crime of cyber stalking. An analysis on the legislative framework in Malaysia in relation to the crime shows that there is lacuna in legal provisions pertaining to the issue.